Ecommerce-price-scraper: Pustaka Ekstraksi Harga E-Commerce Indonesia Melalui Web Scraping - Alfarisy, Gusti Ahmad Fanshuri; Richard Owen Hoan; Helmi; Nur Ali Rajab; Bhagavatgita Mahardika Kesuma Putra (Jurusan Matematika dan Teknologi Informasi, 2025)
This research focuses on the development of a Python library based on BeautifulSoup for automating web scraping on e-commerce platforms Lazada and Bukalapak. The primary goal of this study is to provide a practical solution for efficiently extracting product prices without the need to switch between platforms. The methodology involves integrating BeautifulSoup and Selenium to ensure accurate data retrieval, even when the HTML structure of the sites frequently changes. The developed system is capable of extracting information such as product names, prices, and product links based on user search keywords. The results demonstrate that the library can automate the data retrieval process with high accuracy while offering opportunities for the development of more complex price comparison applications. Additionally, the library provides developers with functions that can be extended to other e-commerce environments. However, adapting to changes in the HTML structure of e-commerce platforms remains a challenge for future development. This solution is expected to improve the efficiency of online shopping for users.